Social Capital and Youth Development - T, Chong, S. (International Journal of Psychosocial Rehabilitation, 2020)
Positive youth development programmes are often designed for young people of marginalised communities to break the vicious cycles of their low socio-economic status. The notion of social capital which could promote high trust and reciprocity in the social networks has been debated in youth research. Young people who build social capital outside family and friendship realms might be the key construct in enhancing positive youth development in the marginalised community. Thus, this paper aims to examine the concept of social capital as a collective effort and to discuss the concepts of trust and reciprocity as the dimensions of social capital. The authors concluded that both bonding social capital and bridging social capital are beneficial to young people. Especially bridging social capital which makes the broader social connections meaningful for young people. This paper also discusses the two types of bridging and bonding social capital that can be formed within young people. The process of how trust is built and how individuals can cooperate for the benefit of themselves and others also highlighted in this paper. Next, the authors discuss the concept of social capital that promote norms of trust and reciprocal cooperation to work together for the common good. In sum, the element of social capital that embedded in various social networks influences how young people face the challenges in daily life. Positive youth development workers and policymakers could reinvent the youth programmes in which taking social capital component into account for the greater benefits of young people.